TUNING IN TO KIDS UNTUK MENURUNKAN PERILAKU AGRESI IBU TERHADAP ANAK - Arif Wibisana; Anissa Lestari (EMPATI: Jurnal Bimbingan dan Konseling, 2026)
Undang-Undang RI No. 23 Thn. 2002 regulates the protection of children, so that children can be avoided from cruelty, physical abuse, torture and other misbehavior. In fact, physical and verbal aggressive behavior toward children are still often found. One of several strategies to decrease such behavior is to undergo tuning in to kids intervention. The aim of this study is to determine the effectiveness of “tuning in to kids” training in decreasing parents’ aggressive behavior toward their kids. This research is a quasi experimental research with non randomized pretest posttest control group design. The subject of this study consisted of 10 mothers which are divided into two groups. Data collection is performed using “parents’ aggressive behavior toward children scale” (33 items) which is adapted from (Savitri, 2005). Data is analyzed by using independent sample t-test. The result shows that there is a significant difference of mother’s aggressive behavior toward their children score between experimental and control group. It means that tuning in to kids training gives a great effect in decreasing aggressive behavior toward their children.